2021
DOI: 10.5812/aapm.113350
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spinal Analgesia for Labor Pain Compared with Epidural Analgesia

Abstract: Objectives: This study aimed to compare the analgesic effect of single-dose spinal versus epidural analgesia for labor pain to verify if applying a single dose spinal analgesia is an efficient technique for labor pain management as an alternative for epidural analgesia. Methods: A total of 128 women in the active phase of labor were randomly allocated into two groups of spinal analgesia (n = 64) and epidural analgesia (n = 64). The latter received a bolus dose of 16 mL of 0.125% bupivacaine and 50 μg fentanyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Other researchers reported no significant increase in the length of stages of labor by singledose spinal analgesia with 2.5mg hyperbaric bupivacaine plus 50 μg fentanyl. (20) The heterogeneity between studies can be due to the fact that each of these studies used a specific dosage and type of medication for anesthesia. Rahmati et al (20) in their trial used a 0.5 mL (2.5 mg) dosage of hyperbaric bupivacaine 0.5% combined with 50 μg fentanyl and suggested this combination as a safe method for spinal analgesia with no significant complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers reported no significant increase in the length of stages of labor by singledose spinal analgesia with 2.5mg hyperbaric bupivacaine plus 50 μg fentanyl. (20) The heterogeneity between studies can be due to the fact that each of these studies used a specific dosage and type of medication for anesthesia. Rahmati et al (20) in their trial used a 0.5 mL (2.5 mg) dosage of hyperbaric bupivacaine 0.5% combined with 50 μg fentanyl and suggested this combination as a safe method for spinal analgesia with no significant complication.…”
Section: Discussionmentioning
confidence: 99%
“…(20) The heterogeneity between studies can be due to the fact that each of these studies used a specific dosage and type of medication for anesthesia. Rahmati et al (20) in their trial used a 0.5 mL (2.5 mg) dosage of hyperbaric bupivacaine 0.5% combined with 50 μg fentanyl and suggested this combination as a safe method for spinal analgesia with no significant complication. Our results showed that the control group's mean lengths of both first and second stages were even longer than those of the spinal anesthesia group (121 ± 187.68 min vs. 92 ± 152.33 min, and 20.90 ± 26.42 min vs. 14.26 ± 15.96 min, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Spinal anesthesia is used in many elective cesarean deliveries, and epidural anesthesia is still the standard technique for postoperative analgesia for cesarean delivery. 7,8 However, there are contraindications to spinal puncture including thrombocytopenia, anticoagulant therapy, or lumbar disease. For women with these conditions, general anesthesia is conducted, and alternative methods of pain relief are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Of course, the absence of pain after normal vaginal delivery with spinal anesthesia has been proven in many studies and this advantage is very important in terms of maternal comfort and pain relief. [ 18 19 ]…”
Section: Introductionmentioning
confidence: 99%